2019
DOI: 10.1158/0008-5472.can-19-0349
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Pharmacogenomics Analysis of Patient-Derived Xenografts

Abstract: Identifying robust biomarkers of drug response constitutes a key challenge in precision medicine. Patient-derived tumor xenografts (PDX) have emerged as reliable preclinical models that more accurately recapitulate tumor response to chemoand targeted therapies. However, the lack of computational tools makes it difficult to analyze high-throughput molecular and pharmacologic profiles of PDX. We have developed Xenograft Visualization & Analysis (Xeva), an open-source software package for in vivo pharmacogenomic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 57 publications
1
27
0
Order By: Relevance
“…The importance of DNA measurements is supported by the inconsistent conclusions by two independent studies on the same PDX expression array datasets by Gao et al 19 Ben-David et al 26,63 concluded that drastic copy number changes, driven by mouse-specific selection, often occur within a few passages. On the other hand, Mer et al 64 reported high similarity between passages of the same PDX model based on direct correlations of gene expression, consistent with our findings in large, independent DNA-based datasets.…”
Section: Discussionsupporting
confidence: 91%
“…The importance of DNA measurements is supported by the inconsistent conclusions by two independent studies on the same PDX expression array datasets by Gao et al 19 Ben-David et al 26,63 concluded that drastic copy number changes, driven by mouse-specific selection, often occur within a few passages. On the other hand, Mer et al 64 reported high similarity between passages of the same PDX model based on direct correlations of gene expression, consistent with our findings in large, independent DNA-based datasets.…”
Section: Discussionsupporting
confidence: 91%
“…In the past, the lack of common standards for cancer models and chemical compounds, as well as meta-data for quantitative drug response profiles, further prevented the wider translational re-use of such data. Recent data harmonization efforts, such as DrugTargetCommons [122] for compound-target activities, PharmacoDB [123] for cell-based drug response profiles, as well as Cell Model Passports [124] and Xeva [125] for in vitro, ex vivo and in vivo models, are likely make their integrated use more straightforward in the AI models.…”
Section: Expert Opinionmentioning
confidence: 99%
“…However, these computational resources, although proven effective, still suffer the limitations of the original studies as the sparsity of the drug and cell interaction matrices, the effective impossibility to merge drug response data across different screenings, and the criticalities of cancer cell lines as a reliable cancer model (39)(40)(41). To this end, the project for a Patient-Derived Model Database (PDMB) launched in 2012 by the NCI might represent a potential breakthrough as genomic and drug response data directly collected from patients and patientderived xenografts (PDXs) will reproduce more accurately the cancer disease and its environment than any cell line model (42). Furthermore, while novel experimental models are generating more accurate data, advanced computational methods are under development to enhance the analytical potential of existing algorithms.…”
Section: Discussionmentioning
confidence: 99%